Wolf ( Canis lupus ) Predation in Pastoral Livestock Systems: Case Study in Croatia - Nikolina Kelava Ugarković; Zvonimir Prpić; Ana Kaić; Maja Vidić; Ante Ivanković; Miljenko Konjačić (Sustainability, 2023)
The predation of livestock by gray wolf ( Canis lupus hereafter, wolf) is a problem throughout eastern Europe and poses a threat to sustainable pasture-based livestock production in some areas. In Croatia, farmers have alarmed the public with news of frequent wolf attacks in the last decade, and wolves, as protected animals, are perceived as a pest and a threat. The aim of this study was to analyze and present the frequency of attacks and killed/injured domestic animals in Croatia. During the ten-year period (2010–2020), 13,359 attack events were reported, where it was determined, with certainty, that the attack was by the wolf. In these attacks, 19,111 domestic animals were killed and 4634 were injured. Predation events occurred predominantly (92.71%) in three counties located in southern Croatia (sub-Mediterranean Croatia), whose total area is 11,170 km 2 (19.74% of the total area of Croatia). The most frequently killed species were sheep (64.78% of all killed animals), which was followed by goats (19.28%) and cattle (9.59%). The highest frequency of attacks and animals killed was recorded in the summer followed by spring and autumn, and the lowest was in winter. The majority of attacks (79.57%) occurred in the morning and during the day. The animal with the highest average number killed per attack was sheep (1.64), which was followed by goats (1.38), cattle (0.99), horses (0.94), donkeys (0.95), and guardian dogs (0.92). During the studied period, in the three counties with the most frequent attacks, 11.72% of the average goat population, 6.34% of the cattle population, and 5.61% of the sheep population were killed. Wolf predation in sub-Mediterranean Croatia presents a threat to the population of domestic ruminants dominantly kept in pastoral livestock systems, and additional efforts need to be made to achieve co-existence between the wolf population and farmers.